2010
DOI: 10.1200/jco.2010.30.5474
|View full text |Cite
|
Sign up to set email alerts
|

Phase II Study of Dasatinib in Patients With Advanced Non–Small-Cell Lung Cancer

Abstract: Dasatinib as a single agent had modest clinical activity that was lower than that generally observed in patients with NSCLC who receive chemotherapy. Pleural effusion was an expected and problematic toxicity that was successfully treated with steroids, diuretics, and dose interruptions. Marked activity in one patient and prolonged stable disease in four others suggested a potential subpopulation of patients with dasatinib-sensitive NSCLC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
105
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 147 publications
(109 citation statements)
references
References 37 publications
4
105
0
Order By: Relevance
“…Concordant with these observations, a later study conducted by Li et al reported that EphA2, EphB2 and EphB4 were identified as targets of dasatinib in lung cancer, using quantitative phosphoproteomics [41]. Although a phase II study of dasatinib in molecular unselected patients with advanced NSCLC unfortunately showed disappointing activity, this inhibitor might be administrated on a potential subpopulation of patients with dasatinib-sensitive NSCLC, or be applied in combination therapy for NSCLC, which needs identification by further studies [42]. Other than multi-target RTK inhibitor, Noberini et al in Pasquale EB's lab identified two isomeric 2, 5-dimethylpyrrolyl benzoic acid derivatives able to selectively inhibit ephrin binding to EphA4 and EphA2 as well as the function of these receptors in live cells [43].…”
Section: Potential Therapeutic Reagents Targeting Ephs/ Ephrins In Lumentioning
confidence: 72%
“…Concordant with these observations, a later study conducted by Li et al reported that EphA2, EphB2 and EphB4 were identified as targets of dasatinib in lung cancer, using quantitative phosphoproteomics [41]. Although a phase II study of dasatinib in molecular unselected patients with advanced NSCLC unfortunately showed disappointing activity, this inhibitor might be administrated on a potential subpopulation of patients with dasatinib-sensitive NSCLC, or be applied in combination therapy for NSCLC, which needs identification by further studies [42]. Other than multi-target RTK inhibitor, Noberini et al in Pasquale EB's lab identified two isomeric 2, 5-dimethylpyrrolyl benzoic acid derivatives able to selectively inhibit ephrin binding to EphA4 and EphA2 as well as the function of these receptors in live cells [43].…”
Section: Potential Therapeutic Reagents Targeting Ephs/ Ephrins In Lumentioning
confidence: 72%
“…QTc prolongation was frequent (>5% of patients experiencing CTCAE scale grade I QTc prolongation) in patients treated with dasatinib, vandetanib, sorafenib, or sunitinib. Dasatinib is used to treat hematological malignancies and has been associated with QTc prolongation in 8% of treated patients (range, 1%–70%), but QTc >500 ms was seen only in <1% 13, 18, 20, 21, 22, 25, 32, 40, 42, 75…”
Section: Resultsmentioning
confidence: 99%
“…The efficacy results and favorable toxicity profile (in particular regarding the hematotoxicity) prompted us to launch a phase II study exploring the efficacy and toxicity of bortezomib single agent in untreated stage IV NSCLC. Such an approach had previously being reported by our group as well as others with innovative compounds [14,15].…”
Section: Introductionmentioning
confidence: 82%